A patient with cerebral Whipple disease with gastric involvement but no gastrointestinal symptoms: a consequence of local protective immunity?. Issue 8 (19th March 2007) - Prüss, Harald; Katchanov, Juri; Zschenderlein, Rolf; Loddenkemper, Christoph; Schneider, Thomas; Moos, Verena
Abstract : Whipple disease is a granulomatous infectious disease caused by Tropheryma whipplei . The bacteria accumulate within macrophages, preferentially in the intestinal mucosa. Disease manifestation seems to be linked to immunological abnormalities of macrophages. We describe a patient with cerebral Whipple disease who presented with changes in mental status, confusion, inverse sleep–wake cycle, bilateral ptosis and vertical gaze palsy. Endoscopic biopsy sampling revealed Whipple disease in the gastric antrum but not in the duodenum. Whole blood stimulation displayed reactivity to T whipplei that was at the lower end of healthy controls while reactivity of duodenal lymphocytes was not diminished. We propose that in cases of neurological symptoms suspicious of Whipple disease with normal duodenal and jenunal findings, biopsy sampling should be extended to the gastric mucosa. The robust reactivity of duodenal lymphocytes may have prevented our patient from developing small bowel disease, whereas the impaired reactivity in peripheral blood lymphocytes might yet explain the bacterial spreading to the central nervous system leading to the rare case of predominant neurological symptoms without relevant systemic involvement.